Association of HLA antigens and total serum immunoglobulin E level with allergic response and failure to respond to ragweed allergen Ra3. - Marsh, D G (1979)
We have applied rigorous statistical analysis to human immune response and HLA data in allergic subjects having varying sensitivity to the minor ragweed allergen, Ra3. By using regression analysis on a series of subsets of Ra3 responders and nonresponders, we obtained data supporting the concept of discrete "responder" and "nonresponder" phenotypes. We found significant positive associations between Ra3 response and total serum IgE and the presence of HLA antigens of the A2 crossreacting group (A2 and A28), and significant negative associations with antigens of the A3 crossreacting group (A3 and A11). Our results suggest that alleles of the HLA-A locus may function either as immune response or immune suppressor genes or that such alleles are epistatic to the response or suppressor genes. Our data add further support to previous findings that HLA-associated specific IgE response is strongly influenced by genetic regulation of basal IgE level.